2020
DOI: 10.3390/microorganisms8020307
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure of Pinus Thunbergii Naturally Infected by the Nematode Bursaphelenchus Xylophilus

Abstract: Pine wilt disease (PWD) caused by the nematode Bursaphelenchus xylophilus is a devastating disease in conifer forests in Eurasia. However, information on the effect of PWD on the host microbial community is limited. In this study, the bacterial community structure and potential function in the needles, roots, and soil of diseased pine were studied under field conditions using Illumina MiSeq coupled with Phylogenetic Investigation of Communities by Reconstruction of Unobserved states (PICRUSt) software. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…macroporum genera in the needles of diseased trees in our study. Moreover, our previous study showed that the abundance of bacteria involved in cellular processes was higher in PWD-affected needles, whereas bacteria with environmental information processing had a higher abundance in healthy needles [ 55 ]. The interaction between fungi and bacteria in PWD-affected needles should not be neglected due to their shared niches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…macroporum genera in the needles of diseased trees in our study. Moreover, our previous study showed that the abundance of bacteria involved in cellular processes was higher in PWD-affected needles, whereas bacteria with environmental information processing had a higher abundance in healthy needles [ 55 ]. The interaction between fungi and bacteria in PWD-affected needles should not be neglected due to their shared niches.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were delivered to the lab on ice and kept at −20 °C for subsequent analysis. The soil physical and chemical properties around diseased and healthy trees were published in our previous study by Ma et al [ 55 ] and were cited as supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominant fungal phylum in Taisui TS-2007S was Ascomycota (relative abundance 87.43%), and the predominant genera were Cyphellophora (10.91%), Cordyceps (10.12%), and Anthopsis (9.46%). However, no microbial phyla or genera with such high levels of abundance have been observed in water and soil (Gilbert et al, 2009;Carvajal et al, 2016;Ma et al, 2020). The microbial community structure of Taisui TS-2007S was obviously different from that in the surrounding environment.…”
Section: Discussionmentioning
confidence: 95%